Public Perceptions of Male Suicide in Digital Platform: A Youtube Comment Analysis and Its Implications for Mental Health Policy - Syari, Suci Fitrah; Habibie, Alfiesyahrianta; Bela, Hafizoh Yuelsa (IDFoS Indonesia, 2025)
Male suicide is a critical mental health issue, as suicide rates among men consistently exceed those of women across many countries, including Indonesia. This problem is exacerbated by persistent stigma surrounding emotional expression and men’s reluctance to seek help. Most research on suicide has predominantly focused on psychological and clinical approaches. This study shifts the emphasis toward understanding public perceptions in order to examine how society interprets, stigmatizes, or expresses empathy toward male suicide. In the digital era, YouTube has become a space where the public articulates responses. This study aims to analyze public perceptions of male suicide through comments on the YouTube video “Bangkit Menjalani Hidup Setelah Gagal Bunuh Diri” from the Menjadi Manusia channel and examine their implications for mental health policy. Using a qualitative design, thematic analysis was conducted on more than one thousand public comments selected based on relevance to male suicide. The findings reveal three central themes: (1) Empathy and digital solidarity; (2) Stigma and moral judgment toward male vulnerability; and (3) Critiques of and hopes for mental health policy. These findings indicate that public perceptions are shaped by gendered expectations and structural inequalities in mental health services, contributing to men’s difficulties in recognizing and responding to psychological crises. The study recommends gender-responsive mental health policies that expand service access, strengthen public literacy, and incorporate digital spaces as part of a broader support ecosystem.